Leachate Distribution and Assessment of Groundwater Quality: A Case Study of Rawa Kucing Landfill, Tangerang - Utami, Ika Wahyu; Najih, Muhammad; Putri, Larasati Rizky; Suudi, Bambang Cholis (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
The self-potential (SP) method investigated leachate distribution near Rawa Kucing. Rawa Kucing is the main landfill in Tangerang that burned almost the entire area. A total of 78 SP data points were scattered throughout the study area. The SP values range from -20 to 16 millivolts, dominated by negative values attributed to electrokinetic processes. The results suggest that a highly conductive zone in the study area may have been caused by high contamination from leachate. The possible direction of leachate flow is towards the Cisadane stream, located west of the landfill. On the other hand, a quantitative interpretation of SP was conducted for two profiles, AA’ and BB’. The result shows that the vertical spreading of leachate was found at a depth of h 6,59 and 3,53 meters and H 8,10 and 4,34 meters for AA' and BB', respectively, with an angle of 28,810. Additionally, groundwater samples were collected from four sites near the landfill to assess groundwater quality using physical and chemical analysis. Based on the Indonesian Ministry of Health Regulation, most parameters indicated low contamination. Statistical analysis revealed that the groundwater near the landfill was worthy of consumption. Based on the results, rainfall during the study significantly reduced the concentrations of contaminants in leachate due to dilution.